Comparison of the CytoSorb® 300 mL and Jafron HA380 hemoadsorption devices: an in vitro study - Nierhaus, Axel; Morales, Jesus; Wendt, Daniel; Scheier, Jörg; Gutzler, Dominik; Jarczak, Dominik; Born, Frank; Hagl, Christian; Deliargyris, Efthymios; Mehta, Yatin (Minimally Invasive Therapy & Allied Technologies, 2022)
We performed an analysis of two blood purification systems to determine their performance for removing interleukins (ILs)-6 and 10, tumor necrosis factor (TNF)-α and monocyte chemoattractant protein (MCP)-1 from blood. An in vitro hemoperfusion blood recirculation circuit was used to compare the CytoSorb ® 300 mL (CytoSorbents Inc., Princeton, NJ) and Jafron HA 380 (Jafron Biomedical Co., Ltd., Zhuhai City, China) devices. The removal of purified recombinant human IL-6, IL-10, TNFα and MCP-1 by the adsorbers was compared at various timepoints. Three runs were completed and removal was evaluated as the mean area under the curve (AUC). Both devices showed effective removal of the tested cytokines. IL-6, IL-10, TNFα and MCP-1 were removed faster and to a higher extent by the CytoSorb ® 300 mL device. At maximal time of 12 h, overall removal according to AUC of remaining concentrations was significantly lower with CytoSorb ® 300 mL compared with HA 380 (IL-6: 1075.5 ± 665.9 vs. 4345.1 ± 1499.3 (p = 0.01), IL-10: 5065.7 ± 882.5 vs. 11,939.7 ± 4523.1 (p = 0.03), TNF-α: 6519.9 ± 997.6 vs. 10,303.7 ± 2347.0 (p = 0.03) and MCP-1: 278.9 ± 40.7 vs. 607.3 ± 84.4 (p = 0.001)). Both the CytoSorb ® and the Jafron HA 380 devices are capable of removing cytokines from blood in a benchtop model. The CytoSorb ® 300 device was significantly more efficient achieving the bulk of the removal in the first 120 min.